Proposed Business Strategy For PT. Mec To Develop Market Share In Southern Jakarta (The Indonesian Journal of Business Administration, 2014)
Abstractâ€” Mayestik eye clinic (PT. MEC) is a clinic located in Mayestik, southern Jakarta. Build in 1992 the clinic was meant to channel the desire of some ophthalmologist that wants to practice at a clinic that they can call their own. This clinic was also based on the idea that middle to low income people need a cheaper option for their eye care services. One of the most obvious differences to the stronger player in eye care service is how unknown PT. MEC to the public. From the growth of eye care hospital in Indonesia from 2009 to 2013 we can see that PT. MEC needs to stay relevant to the competitive. The purpose of this research is to identify the strength and weakness of PT. MEC, and to know opportunities and threats in an eye care industry, and finally formulate effective business strategies recommendation. To evaluate the internal condition of PT. MEC, business model canvas and corporate resource analysis are put to use. While on evaluating the threats and opportunities lies in eye care industry, 5C and competitor analysis are put to use. According to the cell position at IE matrix we can then conclude that the more appropriate strategy for PT. MEC are market penetration and product development. From the QSPM calculation we can conclude that market penetration is the more important one. In the end, this research recommends action plan to implement market penetration strategy. Those action plan are: implementing information system, marketing activation, and work culture assimilation.Â Keywords: business strategy, eye clinic, business model canvas